Grammatical Error in Tiffany Young's Songs - Griselda Giovanni Simanjuntak; Wel Son; Nurma Dhona Handayani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
One of the languages that human beings need in order to communicate with the others is the English language. Learning the English language can be taught through songs. However, the learners need to be more careful because the grammar in songs is not always correct. Because of its incorrectness, the researchers of this research decide to choose Tiffany Young’s songs as some of her songs that contain grammatical errors. This research is designed in the descriptive qualitative because the data sources are written in the lyrics. The aim of this study is to find the grammatical errors in Tiffany Young’s songs. From the analysis, the researchers have found sixteen data that consist of grammatical errors. As the result, researchers confirm that there are grammatical errors in Tiffany Young’s English song lyrics in the form of article noun, negative predicate, auxiliary verb, and three kinds of tenses which are simple future tense, present perfect, and simple present tense.